Cleo: 2013 2013
DOI: 10.1364/cleo_qels.2013.qtu2a.4
|View full text |Cite
|
Sign up to set email alerts
|

Rainbow Trapping in Hyperbolic Metamaterial Waveguide

Abstract: The recent reported trapped ''rainbow'' storage of light using metamaterials and plasmonic graded surface gratings has generated considerable interest for on-chip slow light. The potential for controlling the velocity of broadband light in guided photonic structures opens up tremendous opportunities to manipulate light for optical modulation, switching, communication and light-matter interactions. However, previously reported designs for rainbow trapping are generally constrained by inherent difficulties resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 36 publications
2
29
0
Order By: Relevance
“…As the electric and magnetic resonant frequencies of MMPAs are determined by their geometry, the conventional MMPAs can only produce certain electric and magnetic resonances at the specific wavelengths [13], which restricts their practical applications. For this, several schemes concentrating on dual-band absorption [14][15][16], multiband absorption [17,18], and broadband light absorption at terahertz frequencies [19][20][21][22][23][24] generated by MMPAs have been demonstrated, which are more conducive to high-integration optoelectronic applications. For instance, Cui et al [21] have demonstrated an ultra-broadband thin-film infrared absorber made of saw-toothed anisotropic metamaterial by etching an MM slab into a sawtooth shape with the tooth widths increasing gradually from top to bottom.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the electric and magnetic resonant frequencies of MMPAs are determined by their geometry, the conventional MMPAs can only produce certain electric and magnetic resonances at the specific wavelengths [13], which restricts their practical applications. For this, several schemes concentrating on dual-band absorption [14][15][16], multiband absorption [17,18], and broadband light absorption at terahertz frequencies [19][20][21][22][23][24] generated by MMPAs have been demonstrated, which are more conducive to high-integration optoelectronic applications. For instance, Cui et al [21] have demonstrated an ultra-broadband thin-film infrared absorber made of saw-toothed anisotropic metamaterial by etching an MM slab into a sawtooth shape with the tooth widths increasing gradually from top to bottom.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Cui et al [21] have demonstrated an ultra-broadband thin-film infrared absorber made of saw-toothed anisotropic metamaterial by etching an MM slab into a sawtooth shape with the tooth widths increasing gradually from top to bottom. In another example, Hu et al [24] reported that the trapping "rainbow" storage of light with metamaterials and plasmonic graded surface gratings produces broadband light absorption by controlling the velocity of light in guided photonic structures. Nevertheless, these structures inevitably become increasingly complex when two or more sub-resonators operating at different wavelengths are compacted in a composite unit cell for the multispectral absorption, which limits practical device applications.…”
Section: Introductionmentioning
confidence: 99%
“…We remark that the current problem has an analogue in electromagnetic setting for TMpolarised waves in two-dimensional waveguide with perfectly-electric conducting surfaces in which µ represents the effect of a dielectric 18,19 . In accordance with the use of a continuum model (6) to describe the microstructure of the array, the terraced upper boundary of the metamaterial cavity illustrated in Fig.…”
Section: Description Of the Problemmentioning
confidence: 99%
“…We find that despite a 20 % fluctuations in the metal thickness, both homogeneous and inhomogeneous (discussed below) HMM devices exhibit only a small shift in the absorption spectrum (< 5 %) with the absorptance being essentially unchanged, within the spectral range of interest (1 eV-1.5 eV). The linear/tapered air trenches can be produced by advanced lithographic methods, including electron beam lithography, laser beam direct writing, and focused ion beam milling/lithography/direct deposition [2]- [5], [37]- [39]. The vertical interconnect technology, as a mature process in integrated circuits (ICs), may be used to connect different superlattices for collecting hot electrons to loading circuit.…”
Section:  mentioning
confidence: 99%